IDENTIFIKASI JENIS AKUIFER AIR TANAH MENGGUNAKAN VERTICAL ELECTRICAL SOUNDING KONFIGURASI SCHLUMBERGER - Arif Wijaya; Amirin Kusmiran (JFT : Jurnal Fisika dan Terapannya, 2021)
The availability of clean water is a basic need to meet daily needs. Therefore, the identification of groundwater and its aquifer types was carried out in Labulia, Alor sub-village, Central Lombok Region and Lilir sub-village, Membalan Village, West Lombok Region. The identification of groundwater and the type of aquifer is carried out using the vertical electrical sounding method with the Schlumberger configuration because this method can identify vertical resistivity more accurately than other resistivity methods, such as Wenner. The pseudo resistivity data obtained from these measurements is processed using IPI2Win software and progress. The result of the interpretation was that the aquifer in Olor Agung sub-village was a confined aquifer, while Lilir sub-village was a free aquifer.